Diastolic function of the left ventricular in athletes with small abnormalities of heart development. - G. V. Dzyak; O. B. Nekhanevich (Medičnì Perspektivi)
The purpose of our research was studying of cardiovascular system overexertion symptoms by dynamic of diastolic function of left ventricle during exercises of different power in athletes with small abnormalities of heart development. Wesurveyed 70 athletesaged 12-27 years.Thediastolicfunctiondynamicsof leftventricularisshowedinthework. Themainindexesofmyocardiumrelaxationdisorders duringdiastolearedefined.Itisprovedthatinathleteswithsmall abnormalities of heart development (mitral valve prolapse, open oval window) during submaximal physical loadings, signs of left ventricular diastolic dysfunction developed.